PENGEMBANGAN VIDEO PEMBELAJARAN MATERI PERPINDAHAN KALOR MENGGUNAKAN POWTOON - Ridha Lugiana Utari; Elly Sukmanasa; Lina Novita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to produce a video product for learning heat transfer material using Powtoon in class V of SDN Panaragan 2 Bogor City with a total of 28 students. This product development uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research began by conducting a needs analysis, curriculum analysis, student analysis, creating a product design, then developing a learning media product, then carrying out expert validation, after that conducting a limited trial of learning videos on heat transfer materials using Powtoon on predetermined respondents. The results of validation research from material experts, language experts and media experts show that valid video learning media using Powtoon is very suitable for use, obtaining an average percentage of 96%. At the trial stage, there were limited to 28 students who responded very well and were very suitable for use by obtaining an average percentage of 92.3%. Based on the research results, it can be concluded that the video learning material on heat transfer using Powtoon developed in this research has proven to be valid, easy and interesting for students to use and is very worthy of study.